Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1212/wnl.53.4.715
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and imaging features of cortical malformations in childhood

Abstract: This study illustrates the spectrum of MCD in a pediatric cohort and highlights some of the differences between pediatric and adult patients. Patients with MCD presenting in childhood have a wider spectrum of malformations and more varied, often more severe, clinical manifestations. The lesions are frequently multifocal or generalized and many are associated with noncortical developmental brain anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0
7

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(123 citation statements)
references
References 28 publications
(6 reference statements)
4
112
0
7
Order By: Relevance
“…In this study, Development delay was reported in 53.6% patients of study group i.e. in patients with central nervous system malformations.This result is in agreement with that of Leventer et al, who reported developmental delay or intellectual disability in 68% cases [14] . In a study conducted by Sanghvi et al 19% of the studied patients had normal neuro-developmental assessment, 64% patients had global delay in milestones and 17% had motor delay [15] .…”
Section: Discussionsupporting
confidence: 94%
“…In this study, Development delay was reported in 53.6% patients of study group i.e. in patients with central nervous system malformations.This result is in agreement with that of Leventer et al, who reported developmental delay or intellectual disability in 68% cases [14] . In a study conducted by Sanghvi et al 19% of the studied patients had normal neuro-developmental assessment, 64% patients had global delay in milestones and 17% had motor delay [15] .…”
Section: Discussionsupporting
confidence: 94%
“…9,19,20,[24][25][26][27]29 The abnormality most frequently found in MCD was decreased NAA or NAA/Cr in the lesion compared with a that in the control group, 9,20,[22][23][24]27,28,31 in agreement with our results, but some articles reported cases presenting a normal NAA peak in MCD compared with that in a control group. 21,29,30 This observation might be explained by the fact that these authors used single-voxel MR spectroscopy with a larger voxel volume size (3-8 cm 3 ) than the one used in our study (2.25 cm 3 ). This larger voxel may be influenced more intensely by partial volume averaging, and that could potentially affect the sensitivity of the method to subtle abnormalities.…”
Section: Controls Patientsmentioning
confidence: 85%
“…11 Widespread use of MR imaging allowed recognition of these abnormalities in vivo and their further categorization from a radiologic standpoint. [2][3][4][12][13][14] MR spectroscopy has been used in patients with intractable …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to retrieve only a few population-based study on lissencephaly type I (43) and schizencephaly (44), most reports were published on cohorts (45,46), and were unsuitable for the estimation of the epidemiology of these abnormalities in a given population. Our efforts, therefore, to provide population-based data on the epidemiology of these malformations appear to be a new challenging endeavour.…”
Section: Epidemiology Of Malformations Of Cortical Development (Neuromentioning
confidence: 99%